Real time Raman imaging to understand dissolution performance of amorphous solid dispersions - Tres, Francesco; Treacher, Kevin; Booth, Jonathan; Hughes, Les P.; Wren, Stephen A.C.; Aylott, Jonathan W.; Burley, Jonathan C. (Elsevier, 2014)
We have employed for the first time Raman spectroscopic imaging along with multi-variate curve resolution (MCR) analysis to investigate in real time and in-situ the dissolution mechanisms that underpin amorphous solid dispersions, with data being collected directly from the dosage form itself. We have also employed a novel rotating disk dissolution rate (RDDR) methodology to track, through the use of high-performance liquid chromatography (HPLC), the dissolution trends of both drug and polymer simultaneously in multi-component systems. Two formulations of poorly water-soluble felodipine in a polymeric matrix of copovidone VA64 which have different drug loadings of 5% and 50% w/w were used as models with the aim of studying the effects of increasing the amount of active ingredient on the dissolution performance. It was found that felodipine and copovidone in the 5% dispersion dissolve with the same dissolution rate and that no Raman spectral changes accompanied the dissolution, indicating that the two components dissolve as single entity, whose behaviour is dominated by water-soluble copovidone. For the 50% drug-loaded dispersion, partial RDDR values of both felodipine and copovidone were found to be extremely low. MCR Raman maps along with classical Raman/X-ray powder diffraction (XRPD) characterisation revealed that after an initial loss of copovidone from the extrudate the drug re-crystallises, pointing to a release dynamics dependent on the low water solubility and high hydrophobicity of felodipine. Raman imaging revealed different rates of transition from amorphous to crystalline felodipine at different locations within the dosage form.